2017
DOI: 10.1155/2017/3098198
|View full text |Cite
|
Sign up to set email alerts
|

Research on Spatial Channel Model for Vehicle-to-Vehicle Communication Channel in Roadside Scattering Environment

Abstract: In this paper, an extension of spatial channel model (SCM) for vehicle-to-vehicle (V2V) communication channel in roadside scattering environment is investigated for the first time theoretically and by simulations. Subsequently, to efficiently describe the roadside scattering environment and reflect the nonstationary properties of V2V channels, the proposed SCM V2V model divides the scattering objects into three categories of clusters according to the location of effective scatterers by introducing critical dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…In practical V2V scattering environments as shown in Figure 1, scatterers are intensively distributed in terms of clusters along the roadside since subpaths have similar AoD, AoA, and latency in a cluster [11]. Furthermore, prior studies have shown that the number and position of scatterers seriously affect the signal propagation of V2V channels [22,26].…”
Section: Extended Scm V2v Channel Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…In practical V2V scattering environments as shown in Figure 1, scatterers are intensively distributed in terms of clusters along the roadside since subpaths have similar AoD, AoA, and latency in a cluster [11]. Furthermore, prior studies have shown that the number and position of scatterers seriously affect the signal propagation of V2V channels [22,26].…”
Section: Extended Scm V2v Channel Modelmentioning
confidence: 99%
“…Under the scenarios of V2V communication, both Tx and Rx may be in motion and lower than scatterers on surrounding buildings. In fact, the moving scatterers, e.g., moving cars and pedestrians, have nonignorable impact on V2V channel statistics as described in [10][11][12]. Furthermore, the influence of changes in both angles and velocities of Tx and Rx could cause the nonstationary properties of V2V channels [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical stochastic distributions, e.g., the uniform distribution [16,17], Von Mises distribution [18,19], and Von Mises-Fisher distribution [20], have always been assumed to characterize the angular parameter to achieve the closed-form representation of channel statistical properties. But the AOAs in [16][17][18][19][20] are not modeled as time-variant functions. It is not suitable for the real-time mobile behavior modeling; the temporal variations of the angle parameters need to be included in these models.…”
Section: Introductionmentioning
confidence: 99%
“…In practical V2V environments, scatterers are intensively distributed in terms of clusters along the roadside since subpaths have similar angle of departure (AoD), angle of arrival (AoA), and latency in a cluster [18][19][20][21]. For 3D V2V channel modeling, the conventional 2D models only consider the propagation path in the horizontal plane, which cannot be directly taken into account owing to the elevation angle in 3D space.…”
Section: Introductionmentioning
confidence: 99%